Of Water Cultures: Finding an Architectural Approach to Revitalizing, Supporting and Creating Water Cultures - Rakiep, Tauhir (School of Architecture, Planning and Geomatics, 2023)
Water is essential to human sustenance, a vital resource. Water is leisure, a secondary comfort that supports lifestyle. Water is a destroyer, showing no mercy to anything in its path. Water is an entity that exists despite of; and transcending its physicality. But then why is water treated with such indifference? Within this inquiry I will be researching Water Cultures to understand our current development of the built environment and how we have designed to accommodate, manage and treat water. I will investigate ways that we can endure the overwhelming vastness of the natural environment within our understanding of our own minuteness. The project locates itself at the Strandfontein Pavilion a public area aimed at creating a safe space for beach goers in my hometown, Strandfontein Village, Mitchell's Plain an area on the periphery of Cape Town, wanting to enjoy the ocean. My experience of living in Strandfontein has revealed a disconnect from that ocean. Residents are removed from the resources of the city centre and are dislocated from the natural resources of the environment. This project will encourage a reconnection to the ocean through creating space for the community to experience ways of cultivating and harvesting the resources of the ocean in an informal environment and sharing knowledge passively by existing in spaces with active human presence. This connection will empower the community and grant partial autonomy from the city for residents by bringing some of those resources close to home. The project will use water as a variable that impacts the architectural design to accommodate and manage water and the way that it is experienced by visitors.